Exploring the predictive role of personal identity in trait anxiety: network and Bayesian evidence from Chinese college students - Huang, Ruizhi; Yuan, Ye; Shen, Huiqing; Sun, Yuqi; Wang, Zhilin; Qiu, Huilin; Jeong, Jaesik; Yan, Wenjing; Jiang, Ke (Frontiers in Psychology, 2025)
IntroductionPersonal identity, defined as the perceived continuity and coherence of the self over time, has been theorized to influence anxiety. This study investigates whether personal identity predicts trait anxiety and examines the mediating roles of personality traits and meaning in life.MethodsA total of 613 Chinese college students completed standardized questionnaires, including the State-Trait Anxiety Inventory (STAI), Self-Identity Scale (SIS), Eysenck Personality Questionnaire (EPQ), and the Meaning in Life Questionnaire (MLQ). Data were analyzed using adaptive LASSO network analysis and Bayesian modeling.ResultsPersonal identity showed strong predictive power for trait anxiety in both network and Bayesian models. It demonstrated centrality in the anxiety-related psychological network, with high predictive accuracy in Bayesian classification (88.6%).DiscussionThe findings suggest that a stable and coherent sense of personal identity may protect against anxiety. Conceptually, anxiety is interpreted as arising from disruptions in self-synthesis. These results provide evidence for identity-based approaches to understanding and managing anxiety in university student populations.